1995
DOI: 10.1093/mnras/274.3.964
|View full text |Cite
|
Sign up to set email alerts
|

Approximate input physics for stellar modelling

Abstract: We present a simple and e cient, yet reasonably accurate, equation of state, which at the moderately low temperatures and high densities found in the interiors of stars less massive than the Sun is substantially more accurate than its predecessor by Eggleton, Faulkner & Flannery. Along with the most recently available values in tabular form of opacities, neutrino loss rates, and nuclear reaction rates for a selection of the most important reactions, this provides a convenient package of input physics for stell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
533
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 571 publications
(538 citation statements)
references
References 17 publications
5
533
0
Order By: Relevance
“…7 A comparison among these population synthesis models and observations has been already performed by Noel et al (2013), and it was found that these models disagree -being in general too red -with the integrated colours of superclusters for ages between ∼ 10 8 and ∼ 10 9 years. than those of Pols et al (1995), which were implemented in Vazdekis et al (1996), and those of Dotter et al (2008) (see also An et al 2009). As their temperatures are higher the Padova00 VLM stars are brighter than the ones we employ here for the BASTI models (see figure 5 in Vazdekis et al 2012).…”
Section: Isochronesmentioning
confidence: 99%
“…7 A comparison among these population synthesis models and observations has been already performed by Noel et al (2013), and it was found that these models disagree -being in general too red -with the integrated colours of superclusters for ages between ∼ 10 8 and ∼ 10 9 years. than those of Pols et al (1995), which were implemented in Vazdekis et al (1996), and those of Dotter et al (2008) (see also An et al 2009). As their temperatures are higher the Padova00 VLM stars are brighter than the ones we employ here for the BASTI models (see figure 5 in Vazdekis et al 2012).…”
Section: Isochronesmentioning
confidence: 99%
“…Finally, an (unpublished) EoS (Weiss 1999) consisting of the merging of OPAL-tables, the Saumon-Chabrier EoS (Saumon et al 1995), and that by Pols et al (1995) has been developed; it is available for pure H/He-mixtures only due to the restriction of the Saumon-Chabrier tables. The choice between all these EoS table sets is done before compilation as a pre-compiler option.…”
Section: Equation Of Statementioning
confidence: 99%
“…V568 Lyr, in particular, gives us the opportunity to estimate the age of the cluster. We made with the ev code (Eggleton & Kiseleva-Eggleton 2002) and its much more powerful twin variant (Yakut & Eggleton 2005;Eggleton 2006Eggleton , 2010, both of which are based on the Cambridge stars code (Eggleton 1971(Eggleton , 1972(Eggleton , 1973Pols et al 1995).…”
Section: Modelling and Discussionmentioning
confidence: 99%